L’évolution des divers types d’homicides au Québec de 1954 à 1989 - Grenier, Sylvie (Criminologie, 1993)
In this article, the author describes the evolution of diverse types of homicides committed in Quebec from 1954 to 1989. The four main categories dealt with are : the settling of accounts, quarrelsome and vindictive homicides, homicides associated with another crime, and familial and passion homicides.The author shows that each of these forms of homicide have a particular evolution. The percentage of settlings of accounts greatly increased between 1968 and 1976 and differs from other categories in that it involves a series of homicides linked with gang wars (Cordeau, 1991). Quarrelsome and vindictive homicides triple between 1968 and 1975, whereas familial and passion homicides only doubled during this period. With regard to homicides associated with another crime, contrary to the other categories of homicides and violent crime, it stabilized from 1968 on, but knew a relatively large increase between 1954 and 1968.Finally, the author mentions that these changes bear little resemblance from one category to the other, involving considerable variations through the years in each of these categories of homicides.